2012
DOI: 10.1152/ajprenal.00362.2011
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of renin expression by the orphan nuclear receptors Nr2f2 and Nr2f6

Abstract: Understanding the transcriptional mechanisms of renin expression is key to understanding the regulation of the renin-angiotensin system. We previously identified the nuclear receptors RAR/RXR and Nr2f6 (EAR2) as positive and negative transcriptional regulators of renin expression, respectively (Liu X, Huang X, Sigmund CD. Circ Res 92: 1033-1040, 2003). Both mediate their effects through a hormone response element (HRE) within the renin enhancer. Here, we determined whether another nuclear receptor, Nr2f2 (Coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 41 publications
2
20
1
Order By: Relevance
“…The sentinel SNP is annotated within a CCCTC-binding factor-binding site, identified by ChIP-seq. We note that the CCCTC-binding factor has also been shown to regulate the renin gene 71 and the angiotensinconverting enzyme 2 gene, 72 CCCTC-binding factor-binding sites are ubiquitous in the genome; however, this regulatory mechanism might be worth further investigation. By contrast, Online Figure II shows how ENCODE can highlight evidence of cell-type-specific regulatory elements.…”
Section: Encode: Unraveling the Function Of The Genomementioning
confidence: 92%
“…The sentinel SNP is annotated within a CCCTC-binding factor-binding site, identified by ChIP-seq. We note that the CCCTC-binding factor has also been shown to regulate the renin gene 71 and the angiotensinconverting enzyme 2 gene, 72 CCCTC-binding factor-binding sites are ubiquitous in the genome; however, this regulatory mechanism might be worth further investigation. By contrast, Online Figure II shows how ENCODE can highlight evidence of cell-type-specific regulatory elements.…”
Section: Encode: Unraveling the Function Of The Genomementioning
confidence: 92%
“…22 Multiple studies have shown that VDR, Nr2f2, and Nr2f6 are negative regulators of renin expression. 16,19,23,24 To date, however, there is no report on the role of Hnf4α and ERα in regulating renin expression. We first determined whether these two nuclear receptors are expressed in the renin-expressing As4.1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…A probe where the critical nucleotides in the HRE were mutated was used as a control. 19 ERα protein was detected in proteins eluted from the WT probe but not from the MUT probe, signifying that ERα is able to bind to the HRE sequence with high specificity (Figure 4A). Nr2f2 served as the positive control since we showed it can bind to the HRE in previous studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, COUP-TFII was identified as a yeast onehybrid screen hit with the enhancer HRE and As4.1 cell nuclear extracts (33). Recently, the interaction of COUP-TFII with the renin enhancer HRE repeat was confirmed (35). COUP-TFII is an orphan nuclear receptor that could regulate the expression of its target genes either positively or negatively (29).…”
Section: Discussionmentioning
confidence: 99%